2018
DOI: 10.1158/1055-9965.epi-17-0728
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Characterization of Endometrioid, Clear Cell, and High-Grade Serous Epithelial Ovarian Carcinoma

Abstract: Endometrioid carcinoma (EC) and clear cell carcinoma (CC) histotypes of epithelial ovarian cancer are understudied compared with the more common high-grade serous carcinomas (HGSC). We therefore sought to characterize EC and CC transcriptomes in relation to HGSC. Following bioinformatics processing and gene abundance normalization, differential expression analysis of RNA sequence data collected on fresh-frozen tumors was completed with nonparametric statistical analysis methods (55 ECs, 19 CCs, 112 HGSCs). Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…Similar to our study, transcriptomic analysis revealed the expression profiles of ovarian cancer subtypes. Fridley et al performed RNA-seq to identify differentially expressed genes in HGSC, CCC, and endometrioid carcinoma (EC) [23]. In this report, increased expression levels of FBXO8 , RAPH1 , CEP44 , KIAA0513 , FAM155A , and RXFP1 were found in CCC compared to HGSC, similar to our study.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, transcriptomic analysis revealed the expression profiles of ovarian cancer subtypes. Fridley et al performed RNA-seq to identify differentially expressed genes in HGSC, CCC, and endometrioid carcinoma (EC) [23]. In this report, increased expression levels of FBXO8 , RAPH1 , CEP44 , KIAA0513 , FAM155A , and RXFP1 were found in CCC compared to HGSC, similar to our study.…”
Section: Discussionsupporting
confidence: 89%
“…[ 212 ] The comparative molecular studies that fail to recognize the histopathological origins are no longer effective. [ 150,213 ] Novel ovarian cancer cell models are ongoing need to reflect the main scientific aspects for precise oncology remodeling in vitro, such as cancer cell behaviors, exosomes, and acquired chemoresistance, cell–cell coculture and cell–ECM interactions, and tumor spheroids formation, which elaborately recapitulate cell–cell and cell–ECM interactions in ovarian cancer development, progression, metastasis, dissemination or therapeutic recurrence and relapse. To capture the oncogenic drivers and tumor biology of HGSOC, fallopian tube‐based model systems may define the physiology and susceptibility of this epithelium to tumorous transformation.…”
Section: Conclusion and Outlook For Futurementioning
confidence: 99%
“…18 Accumulating evidence proved that CCNB2 was overexpressed in various human cancers, such as lung cancer, colorectal adenocarcinoma, and ovarian carcinoma. [19][20][21] Moreover, it has been found that advanced clinical stage and worse metastasis status were associated with the elevated expression of circulating CCNB2. 22 As a biomarker, it has been reported that overexpression of CCNB2 could act as an independent predictor of poor prognosis in patients with lung adenocarcinoma and breast cancer.…”
Section: Discussionmentioning
confidence: 99%